Design of a Simple Dust Removal System for a Solar Street Light System (Baghdad Science Journal, 2022)
Dust and bird residue are problems impeding the operation of solar street lighting systems, especially in semi-desert areas, such as Iraq. The system in this paper was designed and developed locally using simple and inexpensive materials. The system runs automatically. It Connects to solar panels used in solar street lighting, and gets the required electricity from the same solar system. Solar panels are washed with dripping water in less than half a minute by this system. The cleaning period can also be controlled. It can also control, sensing the amount of dust the system operates. The impact of different types of falling dust on panels has also been studied. This was collected from different winds and studied their impact on solar panel performance. Also it studied permeability with the wavelength of three types of soil. The system has relatively low current and voltage consumption; it can be generalized for easy manufacturing and locally available components and is well effective.